Navigating tattooed women's bodies : intersections of class and gender - Dann, Charlotte (Emerald Publishing Limited, 2021)
Although tattoos have become increasingly available to us, there are still spaces where they are not accepted, and even 'othered'. Looking at the UK, where media discourses are often unfavourable towards tattooed women discussing their own bodies, this book explores how we understand tattooed women's bodies in the UK - through the lens of gender and class. Unpacking themes which focus on how femininity is embodied, and how unwritten rules are broken or followed, Charlotte Dann demonstrates how meaning is key to our understanding of female body art. Drawing our attention to how traditional constructions of femininity are conformed to and resisted against, Dann positions media discourses of trends, regret, and transformation alongside tattooed women's own thoughts of their tattoos. The chapters uncover how tattoos relate to the embodiment, or resistance, of femininity where the body plays a complex role - in care, in the community, and in families. Delving into the societal norms about what women should and shouldn't do with their bodies, and looking specifically at motherhood, employment, and consumption, Dann demonstrates how meaning-making is critical to how women's tattooed bodies are understood, and how personal narratives take centre stage in the justification for tattoos. Providing a fuller understanding of the nuances particular to tattooed women, this book equips readers to reconstruct how we theorize femininity and the body.
Keywords: Tattooing -- Social aspects -- Great Britain.; Tattooed women -- Great Britain.; Body image in women.; Sex role -- Great Britain.; Femininity -- Great Britain.; Social Science -- Women's Studies.; Cultural studies.; elektronické knihy; electronic books